Back to the Wild: On a Quest for Donors Toward Salinity Tolerant Rice - Solis, Celymar A.; Yong, Miing T.; Vinarao, Ricky; Jena, Kshirod; Holford, Paul; Shabala, Lana; Zhou, Meixue; Shabala, Sergey; Chen, Zhong-Hua (Frontiers in Plant Science, 2020)
Salinity stress affects global food producing areas by limiting both crop growth and yield. Attempts to develop salinity-tolerant rice varieties have had limited success due to the complexity of the salinity tolerance trait, high variation in the stress response and a lack of available donors for candidate genes for cultivated rice. As a result, finding suitable donors of genes and traits for salinity tolerance has become a major bottleneck in breeding for salinity tolerant crops. Twenty-two wild Oryza relatives have been recognized as important genetic resources for quantitatively inherited traits such as resistance and/or tolerance to abiotic and biotic stresses. In this review, we discuss the challenges and opportunities of such an approach by critically analysing evolutionary, ecological, genetic, and physiological aspects of Oryza species. We argue that the strategy of rice breeding for better Na+ exclusion employed for the last few decades has reached a plateau and cannot deliver any further improvement in salinity tolerance in this species. This calls for a paradigm shift in rice breeding and more efforts towards targeting mechanisms of the tissue tolerance and a better utilization of the potential of wild rice where such traits are already present. We summarise the differences in salinity stress adaptation amongst cultivated and wild Oryza relatives and identify several key traits that should be targeted in future breeding programs. This includes: (1) efficient sequestration of Na+ in mesophyll cell vacuoles, with a strong emphasis on control of tonoplast leak channels; (2) more efficient control of xylem ion loading; (3) efficient cytosolic K+ retention in both root and leaf mesophyll cells; and (4) incorporating Na+ sequestration in trichrome. We conclude that while amongst all wild relatives, O. rufipogon is arguably a best source of germplasm at the moment, genes and traits from the wild relatives, O. coarctata, O. latifolia and O. alta, should be targeted in future genetic programs to develop salt tolerant cultivated rice.